Families in modernity: a look from Villavicencio (2020)
The subject of this book is the families analyzed from Villavicencio, which is the capital of Meta, department of Colombia. This city, founded in 1840, had its greatest development in the second half of the twentieth century, as a result of migrations from various regions of the country. Family miscegenation is a phenomenon studied over three generations, from the 1950s to the second of the 21st century. The internal changes of the family structure, its diversification, the rise and decline of patriarchalism and the assimilation of modern values, came with the mass media, radio and television, and were driven by new technologies. These phenomena make visible the transformations of families that are similar to processes found in other national and international contexts. The introduction raises the central thesis and the procedures used in its demonstration in the six chapters of the book.